(untitled) (Scientific journal of the Fergana State University, 2026)
The mineral composition of the aerial part of Mirabilis jalapa L. plant was studied. According to the results, a total of 59 elements were identified, and their overall content amounted to 17164.719 mg/kg. The total concentration of macroelements was 16518 mg/kg, accounting for 96.23% of the determined minerals. The highest proportion belonged to potassium, which made up 43.8% of the total composition. The combined content of micro-, ultramicroelements and rare earth metals was 645.937 mg/kg. Aluminum and iron represented the major fraction of this group, constituting 81.7% of their total mass. Boron, strontium, barium, manganese, titanium, zinc, rubidium, lithium, chromium, nickel, and copper were also found in notable amounts. The results demonstrate that the mineral composition of Mirabilis jalapa L.is rich and diverse. Moreover, the presence of micro- and ultramicroelements enhances its biological significance. These findings may be of great importance in the study of medicinal plants as well as in pharmaceutical and biological research.